POSITIONING PENDIDIKAN IPS DALAM MENGENTASKAN KEMISKINAN SOSIAL - Zuhroh, Ni’matuz (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
There are many factors which contribute to the successful of learning in social science. The factors can be identified as input, process and output. The input factor consists of raw input, instrumental input, and environmental input. The process is related to teaching theory, class management, assignment, evaluation and teaching management. While, out put is related to the progressive development of the student.   This article is an effort to contribute to theory in learning problem of social science; this is by offering an alternative learning approach. The strategy is called as cooperative learning process. This strategy takes four steps, namely: orientation, exploration, depth-understanding, and conclusion. Keyword:  Orientation, Exploration, Depth-understanding, and  Conclusion.